Prevention of Early Marriage Through the Formation of Information and Counseling Center Groups (Pik R) Junior High School 7 Sidoluhur Village Sukaraja Subdistrict Seluma District - Elvi Destariyani; Lela Hartini; Rialike Rialike; Afrina Mizawati (Asosiasi Profesi Multimedia Indonesia, 2023)
Women who married under the age of 16 in Seluma Regency, Bengkulu Province in 2019 with a percentage of 19.49%. The high rate of child marriage causes various health problems including mothers having a 35%-55% high risk of giving birth to babies with low birth weight (LBW).The method of implementing community service activities by forming a group of Youth Information and Counseling Centers (PIK R) SMP 7 Sidoluhur Village, Sukaraja District and continued with counseling on preventing early marriage. The activity was attended by 25 students of SMPN 7 Sidoluhur Village. The activity was carried out in collaboration with BKKBN Bengkulu Province. The results of the activity showed that students' knowledge about early marriage before the intervention was 40% poor, 52% sufficient and 8% good, and after the formation of PIK-R and counseling the level of knowledge was 72% sufficient and 28% good. It is expected that the BKKBN can foster PIK-R activities to increase students' knowledge and awareness of their reproductive health to reduce the incidence of early marriage.